Observations on the Wattles of Adult Helmeted Guinea Fowls (Numida meleagris galeata) - Umosen, A.D.; Onyeanusi, B.I.; Salami, S.O.; Nzalak, J.O.; Imam, J.; Ibe, C.S. (International Journal of Poultry Science, 2008)
Morphological study on the wattles of forty adult male and female (20 each) helmeted guinea fowls weighing between 0.86-1.40kg was undertaken for sexing the birds. The birds were bought from local markets in Zaria. The shape, size and disposition of the wattle were studied grossly. The wattles of helmeted guinea fowl were found to be similar in structure for both sexes but the main difference was the wattle shape, size and angle of inclination in the upper jaw. The differences in the shape and size observed in wattles of heavier adult males were that they appeared elongated, large and folded upwards at their margins. The wattles of the adult males were also observed to be inclined at an angle to the axis of the upper jaw when compared to those of the females. This observation was confirmed in all the birds selected as males and females after slaughter and dissection. It is concluded that a guinea fowl weighing between 0.95-1.40kg with wattle inclined at an angle to the attachment in the upper jaw with upward folded margin is a male guinea fowl.